Aberrant Membrane Structures in Hypervesiculating Escherichia coli Strain ΔmlaEΔnlpI Visualized by Electron Microscopy - Ojima, Yoshihiro; Sawabe, Tomomi; Nakagawa, Mao; Tahara, Yuhei O.; Miyata, Makoto; Azuma, Masayuki (Frontiers in Microbiology, 2021)
Escherichia coli produces extracellular vesicles called outer membrane vesicles (OMVs) by releasing part of its outer membrane. We previously reported that the combined deletion of nlpI and mlaE, related to envelope structure and phospholipid accumulation in the outer leaflet of the outer membrane, respectively, resulted in the synergistic increase of OMV production. In this study, the analysis of ΔmlaEΔnlpI cells using quick-freeze, deep-etch electron microscopy (QFDE-EM) revealed that plasmolysis occurred at the tip of the long axis in cells and that OMVs formed from this tip. Plasmolysis was also observed in the single-gene knockout mutants ΔnlpI and ΔmlaE. This study has demonstrated that plasmolysis was induced in the hypervesiculating mutant E. coli cells. Furthermore, intracellular vesicles and multilamellar OMV were observed in the ΔmlaEΔnlpI cells. Meanwhile, the secretion of recombinant GFP expressed in the cytosol of the ΔmlaEΔnlpI cells was more than 100 times higher than that of WT and ΔnlpI, and about 50 times higher than that of ΔmlaE in the OMV fraction, suggesting that cytosolic components were incorporated into outer-inner membrane vesicles (OIMVs) and released into the extracellular space. Additionally, QFDE-EM analysis revealed that ΔmlaEΔnlpI sacculi contained many holes noticeably larger than the mean radius of the peptidoglycan pores in wild-type E. coli. These results suggest that in ΔmlaEΔnlpI cells, cytoplasmic membrane materials protrude into the periplasmic space through the peptidoglycan holes and are released as OIMVs.